An examination of major works for wind band: the Star-Spangled Banner by Jack Stamp, Tharsos by Jeff Jordan, Americans We by Henry Fillmore and Cajun Folk Songs by Frank Ticheli - Hopkins, Kyle D. (Kansas State University, 2009)
This document was constructed on the comprehensive examination questions based on the Graduate Conducting Recital of Kyle D. Hopkins. The theoretical and historical analysis includes The Star-Spangled Banner by Jack Stamp, Tharsos by Jeff Jordan, Americans We by Henry Fillmore, and Cajun Folk Songs by Frank Ticheli. Along with the analysis, this document contains rehearsal plans and procedures used in the preparation of the literature. The recital was performed in two parts by the McPherson High School Band on February 5, 2009 in the McPherson High School Roundhouse at 7:30 pm and April 30, 2009 in the McPherson High School Auditorium at 7:30 pm.
Keywords: Jack Stamp; Tharsos; Jeff Jordan; Americans We; Cajun Folk Songs; Frank Ticheli; Education, Music (0522); Music (0413)